Active syndromic surveillance program of arboviruses in Rio de Janeiro, Brazil - Mesquita, E. C. (2016)
Fundação Oswaldo Cruz. Instituto Nacional de Infectologia Evandro Chagas. Rio de Janeiro, RJ, Brasil.